Um estudo da concepção dos profissionais de saúde sobre as práticas integrativas e complementares em saúde - Heberlê, Mariluza Oliveira (2013)
The Integrative and Complementary Health Practices propose an effective model of health integral care that privileges the basic health and adopts the promotion of health as its structural axis. The use of integrative practices has increased over the past few years. The study is justified in the lack of knowledge shown by the health teams about the theme and in the importance that it can bring about to the Basic Health Care. The present study intends to answer the question: What‟s the conception about the Integrative and Complementary Health Practices to the professionals that work in Basic Health Units? As bibliographic references were used mainly Pierre Bourdieu, François Laplantine, Madel T. Luz, Nelson Filice de Barros and Charles Tesser, among others. The methodology was a qualitative approach, using semi-structured interviews and participant observation. To analyze the results, it was used the content analysis of Laurence Bardin. The proposal is inserted in the Gender, Body and Health Line of Research, of the UFSM Postgraduate Social Science Program, in the theme Health.